A case report on Duchene muscular dystrophy in an Indian family - Kishor, Saurabh; Verma, Vivek Kumar (International Journal of Research in Medical Sciences, 2022)
Duchenne muscular dystrophy (DMD) is commonest X-linked syndrome muscular dystrophy in the children, present in early childhood and characterized by the proximal muscle weakness and the calf hypertrophy in exaggerated boys. There is generally delay in the motor development and ultimately wheelchair confinement leading to premature death from cardiac or the respiratory complications. For treatment we use various modalities like corticosteroid therapy. We also used intermittent positive pressure ventilation that could help in developments in function, quality of life, ambulation and life expectancy though novel therapies still focus to provide the cure for this disease. Clinically, it is categorized by the progressive muscle wasting ultimately leading to the premature death. Here we presented a case of Duchene muscular dystrophy in a 13 year old boy with clinical presentation.